Diagnostic de sécurité d’une entreprise brésilienne à partir de l’analyse des accidents du travail par la méthode de l’arbre des causes - Binder, M. C.; Pham, D.; Almeida, Ildeberto Muniz de [UNESP] (My University, 1998)
We present here the results of a study of 21 work-related accidents that occurred in a Brazilian manufacturing company. The aim was to assess the safety level of the company to improve its work accident prevention policy. In the last 6 months of 1992 and 1993, all accidents resulting in 15 days' absence from work, reported for social security purposes, were analyzed using the INRS causal tree method (ADC) and a questionnaire completed on site. Potential risk factors for accidents were identified based on the specific factors highlighted by the ADC. More universal trees were also compiled for the safety assessment. Three hundred and thirty specific accident factors were recorded (mean of 15.71 per accident). This is consistent with there being multiple causes of accidents rather than the assertion of Brazilian business safety departments that accidents are due to dangerous or unsafe behavior. Introducing the idea of culpability into accidents prevents the implementation of an appropriate information feedback process, essential for effective prevention. However, the large number of accidents related to material (78%) and environment (70%) indicates that working conditions are poor. This shows that the technical risks, mostly due to unsafe machinery and equipment are not being dealt with. Seventy-five potential accident factors were identified. Of these, 35% were organizational, a high proportion for the company studied. Improvisation occurs at all levels, particularly at the organizational level. This is thus a major determinant for entire series of, if not most, accident situations. The poor condition of equipment also plays a major role in accidents. The effects of poor equipment on safety exacerbate the organizational shortcomings. The company's safety intervention policy should improve the management of human resources (rules designating particular workers for particular workstations; instructions for the safe operation of machines and equipment; training of operators, etc.) and introduce programs to detect risks and to improve the safety of machines and equipment. We also recommend the establishment of a program to follow the results of any preventive measures adopted.
Safety assessment of a Brazilian company based on analysis of work accidents by the causal tree method
Keywords: Brazil; human; industry; occupational accident; occupational health; questionnaire; risk factor; statistics; Accidents, Occupational; Humans; Industry; Occupational Health; Questionnaires; Risk Factors